Simulating the UV escape fractions from molecular cloud populations in star-forming dwarf and spiral galaxies - Howard, Corey S.; Pudritz, Ralph E.; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. The escape of ultraviolet photons from the densest regions of the interstellar medium (ISM) - giant molecular clouds (GMCs) - is a poorly constrained
Published: 20 December 2017
Gesehen am 09.10.2019